MnO2 / ZnTiO3 composite positive electrode material and preparation method and application thereof
By combining MnO2 with ZnTiO3, MnO2/ZnTiO3 composite positive electrode material is formed, which solves the problem of poor structural instability and conductivity of MnO2 in zinc ion batteries, and significantly improves the cycle stability and rate performance of the battery.
Patent Information
- Application Number
- CN202510055465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
MnO2, as the positive electrode material of zinc ion batteries, has poor structural instability and poor conductivity, resulting in poor cycle stability and rate performance.
By compounding with ZnTiO3, the MnO2/ZnTiO3 composite cathode material is formed, and the perovskite structure and electrochemical characteristics of ZnTiO3 are used to improve the electrochemical performance of MnO2.
The cycling stability and rate performance of zinc ion batteries are improved, the structural stability and conductivity of the material are enhanced, the contact between MnO2 and the electrolyte is reduced, and the Mn-soluble problem is avoided.
Smart Images

Figure CN119852368A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of positive electrode materials for zinc ion batteries, and in particular to a MnO2 / ZnTiO3 composite positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles and large-scale storage systems, zinc-ion batteries have attracted much attention as a green energy source. Traditional lithium-ion batteries are constrained by the shortage of lithium resources and low safety. Zinc-ion batteries have obvious advantages. Zinc resources are abundant, safe, and chemically relatively stable, and are not prone to safety accidents. In terms of technological accumulation, research on electrode materials such as manganese dioxide positive electrodes and zinc metal negative electrodes has continued to deepen, and progress has also been made in the research and development of aqueous electrolytes, which can improve performance such as ionic conductivity. In addition, drawing on the experience of other battery structure design provides a direction for improving the performance of zinc-ion batteries.
[0003] In the research of positive electrode materials for zinc-ion batteries, manganese-based oxides are one of the research hotspots. Manganese-based oxides can be roughly divided into MnO2, Mn3O4, Mn2O3 and MnO. Among them, the most studied manganese-based oxide is MnO2, because compared with similar oxides in low oxidation states, the stability of tetravalent manganese ions is higher. MnO2 and others are more suitable as storage media for zinc ions. However, so far, due to its inherent structural instability and slow ion diffusion rate, it has shown poor cycle stability, poor rate performance and large capacity attenuation during the cycle process, which limits its potential high performance. Therefore, it is necessary to modify MnO2, such as composite conductive materials, doping with other atoms and utilizing oxygen vacancies, to improve the electrochemical properties of manganese dioxide, which has become a key issue that needs to be solved urgently. Summary of the invention
[0004] In view of this, the present application provides a MnO2 / ZnTiO3 composite positive electrode material and a preparation method and application thereof. The MnO2 / ZnTiO3 composite positive electrode material, as a positive electrode material for a zinc ion battery, has the function of improving the battery cycle stability and rate performance, and can effectively overcome the technical problem that the battery material MnO2 itself has an unstable structure and poor conductivity, which in turn affects its electrochemical performance.
[0005] The first aspect of the present application provides a method for preparing a MnO2 / ZnTiO3 composite positive electrode material, comprising the following steps:
[0006] (1) dissolving a manganese source and an oxidant in a solvent, stirring to obtain a mixed solution, performing a hydrothermal reaction, washing, and drying to obtain a precursor material;
[0007] (2) dissolving the precursor material, titanium source and zinc source in a solvent, and obtaining a slurry after ball milling;
[0008] (3) After drying the slurry, calcining is performed to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0009] The superior properties of ZnTiO3 as a battery material are mainly due to its structural and electrochemical properties. This material has a perovskite structure, and the octahedron and hole structure provide a direct and stable transmission channel for zinc ions. Given that the high theoretical specific capacity of MnO2 can be exerted after ZnTiO3 and MnO2 are combined, the overall specific capacity of the material is improved, providing the battery with a higher energy storage capacity; therefore, the structure of MnO2 can be strengthened by compounding ZnTiO3 materials, and the structure can be complemented to improve the overall performance of the battery.
[0010] Preferably, in step (3), the drying temperature is 80 to 300° C. and the drying time is 1 to 24 hours; or
[0011] In step (3), the specific conditions of the calcination are: carried out in a high-temperature furnace under air or nitrogen atmosphere, the calcination temperature is 200-700° C., and the calcination time is 1-24 hours.
[0012] Preferably, in step (2), the ball milling time is 2 to 12 hours, and the ball milling speed is 200 to 2000 rpm.
[0013] Preferably, in step (2), the molar ratio of Mn to titanium source in the precursor material is (1:0.05) to (1:0.5); the molar ratio of the titanium source to the zinc source is 1:(0.8 to 1.2); and the mass ratio of the solvent to the precursor material is 1:(0.5 to 50).
[0014] Preferably, in step (2), the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, titanium oxalate, titanium sulfate, and titanium dioxide; the zinc source is selected from at least one of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, and zinc acetylacetonate; and the solvent is selected from at least one of water, ethanol, ethylene glycol, and acetone.
[0015] Preferably, in step (1), the hydrothermal reaction temperature is 100-250° C., and the hydrothermal reaction time is 2-12 hours. Specifically, the volume of the reactor is one of 50 ml, 75 ml, and 100 ml.
[0016] Preferably, in step (1), the molar ratio of the manganese source to the oxidant is 1:(0.1-10); or
[0017] In step (1), the concentration of the manganese source in the mixed solution is 0.01 to 3.0 mol / L; or
[0018] In step (1), the stirring speed is 50 to 2000 rpm and the stirring time is 1 to 10 hours.
[0019] Specifically, in step (1), the cleaning agent used for washing is one of pure water and ethanol or a mixed solution of the two in a volume ratio of 1:(0.1-5).
[0020] Preferably, in step (1), the manganese source is selected from at least one of manganese chloride, manganese acetate, manganese sulfate, manganese carbonate, manganese nitrate, and manganese oxide; the oxidant is selected from at least one of potassium permanganate, potassium perchlorate, and hydrogen peroxide; and the solvent is selected from at least one of water, ethanol, ethylene glycol, n-butanol, and cyclopentanol.
[0021] The second aspect of the present application also provides a MnO2 / ZnTiO3 composite positive electrode material, which is a MnO2 / ZnTiO3 composite positive electrode material prepared by the above method.
[0022] The third aspect of the present application also provides the use of the above-mentioned MnO2 / ZnTiO3 composite positive electrode material in a zinc ion battery, wherein the MnO2 / ZnTiO3 composite material is used as the active material of the positive electrode of the zinc ion battery.
[0023] Compared with the prior art, this application has the following beneficial effects:
[0024] 1. The method of the present application can achieve uniform compounding and good crystallization of MnO2 and ZnTiO3, reduce production costs, and prepare MnO2 / ZnTiO3 composite materials with stable structures, thereby obtaining materials with both nano-scale active material particles and micron-scale stable structures, thereby achieving the purpose of saving resources, realizing the preparation of high-performance composite materials and low-cost continuous production; the rate performance and cycle capacity of the zinc positive electrode material compositely modified by the method of the present application are greatly improved.
[0025] 2. The present application combines MnO2 and ZnTiO3 materials to dope Zn and Ti elements in MnO2 materials. The doped Zn can improve the stability of the layered structure of MnO2, reduce the degree of lattice deformation of zinc ions during the deintercalation process, and improve the structural stability and specific capacity; while Ti doping can increase the interlayer spacing, making Mn 3+ To Mn 4+ The transformation reduces the Jiang-Taylor effect during the cycle and avoids the change of the bulk phase during the cycle; at the same time, the different valence states of Ti introduced 4+It can improve its electrical conductivity, and thus further improve the structural stability of the main material and the change in conductivity, thereby effectively improving the material's cycle stability and rate performance; in addition, the composite ZnTiO3 material can reduce the contact between MnO2 and the external electrolyte, alleviate the Mn dissolution problem, avoid structural damage to the main material, and improve the cycle stability of the MnO2 material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 The XRD pattern of the MnO2 / ZnTiO3 composite material prepared in Example 1 of the present application;
[0028] Figure 2 The SEM images of the MnO2 / ZnTiO3 composite material prepared in Example 1 of the present application at different magnifications are shown in FIG. Figure 2 aThe magnification is 10.0K, Figure 2 b Magnification is 3.0K;
[0029] Figure 3 The rate cycling performance diagram of Example 1 and Comparative Example 1 of the present application at different current densities;
[0030] Figure 4 This is a cyclic stability performance diagram of Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the application. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0033] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0034] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0035] Example 1
[0036] A method for preparing a MnO2 / ZnTiO3 composite positive electrode material comprises the following steps:
[0037] (1) Add 2.45 g of manganese acetate tetrahydrate and 5 ml of H2O2 (30%) into a beaker, then add 50 ml of pure water, and stir at 500 rpm for 3 h to obtain a mixed solution, then put the mixed solution into a 75 ml hydrothermal kettle, then wash with water, and heat in an oven at 150° C. for 5 h to obtain a precursor material;
[0038] (2) 10 g of the obtained precursor material was mixed with 1.8 g of zinc sulfate and 1.9 g of titanium tetrachloride (0.01 mol), 20 ml of acetone was added, and the mixture was ball-milled at 500 rpm for 3 h to obtain a slurry;
[0039] (3) The slurry after ball milling was placed in an oven and dried at 150°C for 3 h, and then placed in a high-temperature furnace and calcined at 400°C for 6 h in an air atmosphere to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0040] The MnO2 / ZnTiO3 composite positive electrode material prepared in this example was characterized by SEM and XRD. Figure 1 The XRD diagram of the MnO2 / ZnTiO3 composite positive electrode material prepared in Example 1. Through analysis, it is found that most of the diffraction peaks in Example 1 basically correspond to the standard card of MnO2 and the standard PDF card 44-0141. Some characteristic peaks of ZnTiO3 are also shown in Example 1, indicating that ZnTiO3 and MnO2 are successfully composited. Most of the characteristic peaks appearing in the figure are characteristic peaks of MnO2, which correspond to the standard PDF card 44-0141. This proves that the composite of ZnTiO3 and MnO2 has been successfully achieved. SEM picture as shown Figure 2 As shown, from Figure 2 It can be seen that the prepared MnO2 / ZnTiO3 composite positive electrode material is in the shape of long strips with a length of 1-25μm and a diameter of about 100nm, and the material is evenly dispersed.
[0041] Example 2
[0042] A method for preparing a MnO2 / ZnTiO3 composite positive electrode material comprises the following steps:
[0043] (1) Add 1.25 g of manganese chloride and 6.32 g of potassium permanganate into a beaker, then add 25 ml of ethanol and 25 ml of pure water, and stir at 600 rpm for 4 h to obtain a mixed solution, then put the mixed solution into a 100 ml hydrothermal kettle, then wash with a mixed solution of water and ethanol (volume ratio 1:1), and heat in an oven at 120 ° C for 5 h to obtain a precursor material;
[0044] (2) 10 g of the obtained precursor material was mixed with 5.94 g of zinc nitrate hexahydrate and 4.33 g of tetraethyl titanate, and 15 ml of ethanol and 15 ml of acetone were added, followed by ball milling at 600 rpm for 2 h to obtain a slurry;
[0045] (3) The slurry after ball milling was placed in an oven and dried at 160°C for 2 h, and then placed in a high-temperature furnace and calcined at 350°C for 8 h in an air atmosphere to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0046] Example 3
[0047] A method for preparing a MnO2 / ZnTiO3 composite positive electrode material comprises the following steps:
[0048] (1) Add 1.51 g of manganese sulfate and 6.93 g of potassium perchlorate into a beaker, then add 45 ml of pure water, and stir at 700 rpm for 5 h to obtain a mixed solution, then put the mixed solution into a 50 ml hydrothermal kettle, then wash with a mixed solution of water and ethanol (volume ratio 2:1) and heat in an oven at 140 ° C for 5 h to obtain a precursor material;
[0049] (2) 10 g of the obtained precursor material was mixed with 0.73 g of zinc chloride and 6.8 g of tetrabutyl titanate, 20 ml of ethanol was added, and the mixture was ball-milled at 700 rpm for 2 h to obtain a slurry;
[0050] (3) The slurry after ball milling was placed in an oven and dried at 170°C for 2 h, and then placed in a high-temperature furnace and calcined at 300°C for 6 h in an air atmosphere to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0051] Example 4
[0052] A method for preparing a MnO2 / ZnTiO3 composite positive electrode material comprises the following steps:
[0053] (1) Add 1.15 g of manganese carbonate and 10.22 ml of H2O2 (30%) into a beaker, then add 25 ml of ethylene glycol and 25 ml of pure water, and stir at 800 rpm for 6 h to obtain a mixed solution, then put the mixed solution into a 75 ml hydrothermal kettle, then wash with water, and heat in an oven at 130° C. for 5 h to obtain a precursor material;
[0054] (2) 10 g of the obtained precursor material (0.1 mol) was mixed with 3.67 g of zinc acetate (0.02 mol) and 4.48 g of titanium oxalate (0.02 mol), and 15 ml of ethanol and 15 ml of pure water were added, followed by ball milling at a rotation speed of 800 rpm for 2 h to obtain a slurry;
[0055] (3) The slurry after ball milling was placed in an oven and dried at 160°C for 2 h, and then placed in a high-temperature furnace and calcined at 250°C for 8 h in an air atmosphere to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0056] Example 5
[0057] A method for preparing a MnO2 / ZnTiO3 composite positive electrode material comprises the following steps:
[0058] (1) Add 0.71 g of manganese oxide, 0.01 mol, and 15.8 g of potassium permanganate into a beaker, then add 40 ml of ethanol, and stir at 900 rpm for 9 h to obtain a mixed solution, then put the mixed solution into a 50 ml hydrothermal kettle, then wash with a mixed solution of water and ethanol (volume ratio 1:2) and heat in an oven at 220 ° C for 8 h to obtain a precursor material;
[0059] (2) 10 g of the obtained precursor material was mixed with 6.458 g of zinc sulfate and 9.1 g of tetraethyl titanate, and 20 ml of ethanol and 25 ml of pure water were added, followed by ball milling at 900 rpm for 3 h to obtain a slurry;
[0060] (3) The slurry after ball milling was placed in an oven and dried at 250°C for 3 h, and then placed in a high-temperature furnace and calcined at 600°C for 6 h in an air atmosphere to obtain a MnO2 / ZnTiO3 composite positive electrode material.
[0061] Comparative Example 1
[0062] A method for preparing pure MnO2 material comprises the following steps:
[0063] (1) Add 2.45 g of manganese acetate tetrahydrate and 5 ml of H2O2 (30%) into a beaker, then add 50 ml of pure water, and stir at 500 rpm for 3 h to obtain a mixed solution, then put the mixed solution into a 75 ml hydrothermal kettle, then wash with water, and heat in an oven at 150° C. for 5 h to obtain a precursor material;
[0064] (2) 10 g of the obtained precursor material was placed in a high-temperature furnace and calcined at 400°C for 6 h in an air atmosphere to obtain pure MnO2 material.
[0065] Test Case
[0066] The products obtained in the above-mentioned Example 1 and Comparative Example 1 were used as the active material of the positive electrode material to prepare the working electrode, the negative electrode was made of zinc sheet, the electrolyte was made of zinc trifluoromethanesulfonate solution with a concentration of 2.5-3.5 mol / L, and the diaphragm was made of GF / A glass fiber diaphragm to better infiltrate the zinc trifluoromethanesulfonate electrolyte. The zinc ion battery was assembled and then placed in a blue electricity test system to test the battery performance.
[0067] The zinc ion battery prepared by using the MnO2 / ZnTiO3 composite positive electrode material prepared in Example 1 as the electrode material was charged and discharged at different rates (such as Figure 3 As shown, at current densities of 0.2A / g, 0.3A / g, 0.5A / g, 1A / g, 2A / g, and 3A / g, each current density was cycled for 10 cycles, and finally returned to 0.2A / g for 10 cycles. The zinc sub-batteries assembled in Example 1 can maintain specific capacities of about 296mAh / g, 272mAh / g, 245mAh / g, 191mAh / g, 151mAh / g, 131mAh / g, and 310mAh / g, respectively; after multiple cycles, the capacity of the battery decreased slightly, indicating that the assembled battery has good rate performance. The performance of the zinc ion battery made of pure MnO2, the product of Comparative Example 1, as the electrode material, at different rates is much lower than the performance of MnO2 / ZnTiO3, the product of Example 1.
[0068] By comparing the cycle stability performance diagrams of Example 1 and Comparative Example 1, it can be found that ( Figure 4 ), the MnO2 / ZnTiO3 composite material prepared in Example 1 was charged and discharged at a current density of 1.0A / g, and the first-cycle discharge capacity was about 190mAh / g. After 1000 cycles, it still had a reversible capacity of 148mAh / g; while the pure MnO2 material prepared in Comparative Example 1 had a first-cycle discharge capacity of about 171mAh / g at a current density of 1.0A / g, and had a reversible capacity of only 70mAh / g after 1000 cycles; its cycle stability performance was much worse than that of the material prepared in Example 1.
[0069] The product obtained by the method of the present application is used as the positive electrode material of the zinc ion battery. The rate performance and cycle stability of the material are improved by the composite technology with ZnTiO3. The synthesized composite material has good morphology and structure and good stability. It is used for the positive electrode material of the zinc ion battery, and the assembled battery has high rate performance and excellent cycle stability. This is attributed to the fact that the doped Zn can improve the stability of the layered structure of MnO2, and the Ti doping can further improve the structural stability of the main material and the change of the conductivity distance, thereby effectively improving the cycle stability and rate performance of the material. In addition, the composite ZnTiO3 material can reduce the contact between MnO2 and the external electrolyte, improve the cycle stability of the MnO2 material, and thus obtain a high-performance MnO2 / ZnTiO3 composite material.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a MnO2 / ZnTiO3 composite positive electrode material, characterized in that: The following steps are involved: (1) dissolving a manganese source and an oxidant in a solvent, stirring to obtain a mixed solution, performing a hydrothermal reaction, washing, and drying to obtain a precursor material; (2) dissolving the precursor material, titanium source and zinc source in a solvent, and obtaining a slurry after ball milling; (3) After drying the slurry, calcining is performed to obtain a MnO2 / ZnTiO3 composite positive electrode material.
2. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (3), the drying temperature is 80 to 300° C. and the drying time is 1 to 24 hours; or In step (3), the specific conditions of the calcination are: carried out in a high-temperature furnace under air or nitrogen atmosphere, the calcination temperature is 200-700° C., and the calcination time is 1-24 hours.
3. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (2), the ball milling time is 2 to 12 hours, and the ball milling speed is 200 to 2000 rpm.
4. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (2), the molar ratio of Mn to titanium source in the precursor material is (1:0.05) to (1:0.5); the molar ratio of the titanium source to the zinc source is 1:(0.8 to 1.2); and the mass ratio of the solvent to the precursor material is 1:(0.5 to 50).
5. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (2), the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, titanium oxalate, titanium sulfate, and titanium dioxide; the zinc source is selected from at least one of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, and zinc acetylacetonate; and the solvent is selected from at least one of water, ethanol, ethylene glycol, and acetone.
6. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 100 to 250° C., and the hydrothermal reaction time is 2 to 12 hours.
7. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of the manganese source to the oxidant is 1:(0.1-10); or In step (1), the concentration of the manganese source in the mixed solution is 0.01 to 3.0 mol / L; or In step (1), the stirring speed is 50 to 2000 rpm and the stirring time is 1 to 10 hours.
8. The method for preparing the MnO2 / ZnTiO3 composite positive electrode material according to claim 1, characterized in that: In step (1), the manganese source is selected from at least one of manganese chloride, manganese acetate, manganese sulfate, manganese carbonate, manganese nitrate, and manganese oxide; the oxidant is selected from at least one of potassium permanganate, potassium perchlorate, and hydrogen peroxide; and the solvent is selected from at least one of water, ethanol, ethylene glycol, n-butanol, and cyclopentanol.
9. A MnO2 / ZnTiO3 composite positive electrode material, characterized in that: A MnO2 / ZnTiO3 composite positive electrode material prepared by the method described in any one of claims 1 to 8.
10. The use of the MnO2 / ZnTiO3 composite positive electrode material according to claim 9 in a zinc ion battery, characterized in that: MnO2 / ZnTiO3 composite material is used as the active material of the positive electrode of zinc ion battery.